2003
DOI: 10.1046/j.1365-2141.2003.04361.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric myelodysplastic syndromes and juvenile myelomonocytic leukaemia in the UK: a population‐based study of incidence and survival

Abstract: Summary. We aimed to identify and classify cases of paediatric myelodysplastic syndromes (MDS) occurring in Britain to estimate the incidence of this rare group of diseases, investigate the results of therapy and identify prognostic risk factors. Patients aged below 15 years at diagnosis were collected from England, Scotland and Wales, inclusively between 1990 and 1999. One hundred and thirty-five patients were accepted as de novo MDS or juvenile myelomonocytic leukaemia (JMML). The incidence for this period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 31 publications
7
100
1
6
Order By: Relevance
“…Patients with monosomy 7 may represent a subset of patients with different biology, although studies showed the cytogenetic abnormalities including monosomy 7 are not predictive of outcome after first HSCT. 7,31 Third, consistent with previous reports in CML, 32,33 occurrence of GVHD correlated with response to DLI, suggesting a substantial overlap between the GVL effect and GVHD occurrence. It is also noteworthy that in this series of JMML, none of the patients given DLI from a matched sibling donor responded.…”
Section: Discussionsupporting
confidence: 80%
“…Patients with monosomy 7 may represent a subset of patients with different biology, although studies showed the cytogenetic abnormalities including monosomy 7 are not predictive of outcome after first HSCT. 7,31 Third, consistent with previous reports in CML, 32,33 occurrence of GVHD correlated with response to DLI, suggesting a substantial overlap between the GVL effect and GVHD occurrence. It is also noteworthy that in this series of JMML, none of the patients given DLI from a matched sibling donor responded.…”
Section: Discussionsupporting
confidence: 80%
“…Poor prognostic factors include (1) age less than 2 years, (2) low platelet count and (3) elevated fetal hemoglobin levels. 16,84 However, the scientific reasons as to why these factors portend a poor prognosis remain a mystery. Left untreated (which rarely occurs anymore), the natural course of JMML is rapidly fatal with 80% of patients surviving o3 years.…”
Section: Jmmlfpathogenesismentioning
confidence: 99%
“…The score has not been applied to other large series of children with MDS mainly because HbF is not routinely evaluated in MDS patients. 4,7 Poor prognosis in JMML has been associated with low platelet count, elevated HbF, and age at diagnosis of 2 years or more, 1,[10][11][12] confirming two of the factors included in the FPC score. 1 In particular, in the EWOG-MDS experience, a platelet count below 33 Â 10 9 /l at presentation is the strongest negative prognostic factor.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Some patients show a prolonged and stable clinical course without treatment, but most cases will eventually progress. Hematopoietic stem cell transplantation (HSCT) is the treatment of choice, but the outcome following HSCT is jeopardized if disease progression has occurred.…”
Section: Introductionmentioning
confidence: 99%